Increased Frataxin Expression Induced in Friedreich Ataxia Cells by Platinum TALE-VP64s or Platinum TALE-SunTag - Khadija Cherif; Catherine Gérard; Joël Rousseau; Dominique L. Ouellet; Pierre Chapdelaine; Jacques P. Tremblay (Elsevier, 2018)
Frataxin gene (FXN) expression is reduced in Friedreich's ataxia patients due to an increase in the number of GAA trinucleotides in intron 1. The frataxin protein, encoded by that gene, plays an important role in mitochondria's iron metabolism. Platinum TALE (plTALE) proteins targeting the regulatory region of the FXN gene, fused with a transcriptional activator (TA) such as VP64 or P300, were used to increase the expression of that gene. Many effectors, plTALEVP64, plTALEp300, and plTALESunTag, targeting 14 sequences of the FXN gene promoter or intron 1 were produced. This permitted selection of 3 plTALEVP64s and 2 plTALESunTag that increased FXN gene expression by up to 19-fold in different Friedreich ataxia (FRDA) primary fibroblasts. Adeno-associated viruses were used to deliver the best effectors to the YG8R mouse model to validate their efficiencies in vivo. Our results showed that these selected plTALEVP64s or plTALESunTag induced transcriptional activity of the endogenous FXN gene as well as expression of the frataxin protein in YG8R mouse heart by 10-fold and in skeletal muscles by up to 35-fold. The aconitase activity was positively modulated by the frataxin level in mitochondria, and it was, thus, increased in vitro and in vivo by the increased frataxin expression. Keywords: TAL effector, VP64, p300, SunTag, TALE-SunTag, AAV9, frataxin, transcription regulation, initiation of transcription, epigenetics, gene regulation